'Queering Genealogy Through Wills'. (19th March 2015) - Monk, Daniel
Abstract: Wills are an overlooked source. Alongside birth, death and marriage certificates they are official legal texts that provide a record of families, kinship and personal life. They have a particular significance for research about gender and sexuality. This paper, by Daniel Monk, highlights some of the insights that they can provide and discusses the methods (and associated pitfalls) for accessing and reading them.